Psychological burden of hearing-impaired children and their parents through the COVID-19 pandemic - Li, Donglei; Lin, Ken; Cen, Xinru; Fan, Yuwei; Hong, Liping; Wu, Zhao; Chen, Wenliang; Zhong, Xinqi (Frontiers in Public Health, 2024)
Objective Childhood hearing impairment has potential repercussions on the mental well-being of both children and their parents. As a vulnerable population in accessing health care services, they may face specific challenges, especially during the COVID-19 pandemic. This cross-sectional study aims to investigate the association between childhood hearing impairment and the mental health of children and their parents, and to assess health care utilization of hearing-impaired children and its impact on mental outcomes for both during the COVID-19 pandemic. Methods Using the National Health Interview Survey (NHIS) database, we analyzed data for 15,989 children aged 5–17 and their corresponding parents. The correlations between childhood hearing impairment and mental outcomes were examined using logistic regression models. The 2020 (quarter 3 and quarter 4)-2021 NHIS data was singled out and re-analyzed, focusing on the utilization of medical care during the COVID-19 pandemic. Results After accounting for covariates, hearing-impaired children exhibited a higher frequency of anxiety (OR 2.33, 95% CI 1.79–3.02) or depression (OR 2.14, 95% CI 1.59–2.88). Parents of hearing-impaired children had significantly higher odds of a higher frequency of anxiety (OR 1.55, 95% CI 1.20–2.01) or depression (OR 1.73, 95% CI 1.30–2.29). Interaction effect of hearing impairment with survey year on parents’ mental health outcomes was observed (p for interaction <0.1). Children with hearing loss had higher odds of reporting delayed medical care (OR 2.00, 95% CI 1.11–3.59) or canceled medical care (OR 1.96, 95% CI 0.98–3.96, p = 0.059) due to the pandemic. Delayed medical care (OR 12.41, 95% CI 2.78–55.46) or canceled medical care (OR 6.26, 95% CI 1.28–30.75) due to the COVID-19 pandemic significantly contributed to the increase of anxiety frequency in hearing-impaired children. Conclusion Childhood hearing impairment exhibits a substantial impact on children’s and parental mental health, which is further exacerbated by the COVID-19 pandemic. Families of hearing-impaired children appear to be in a vulnerable position during public health emergencies such as the COVID-19 pandemic, which can further exacerbate their mental outcomes.